Edukasi Komplementer SEFT dan SPEOS dalam Mengatasi Kecemasan Serta Meningkatkan Produksi Asi pada Ibu Nifas di Wilayah Puskesmas Sambau Kota Batam - Silvia Mona; Kiki Rizki Dasaryandi; Susanti Susanti; Siti Haminah; Selvi Novira (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
Postpartum anxiety is a psychological problem that often occurs after childbirth and can have a direct impact on decreased breast milk production. Non-pharmacological efforts that can help overcome this are Spiritual Emotional Freedom Technique (SEFT) therapy and Endorphin, Oxytocin, and Suggestive Massage Stimulation (SPEOS). This community service activity aims to improve comfort, calmness, and increase breast milk production through the application of a combination of SEFT and SPEOS therapy to postpartum mothers in the Sambau Community Health Center, Batam City. The activity method is carried out through education, demonstrations, and direct practice with postpartum mothers given to 48 postpartum mothers. The results of the activity showed an increase in mothers' knowledge about SEFT and SPEOS relaxation techniques, about managing anxiety, and how to increase breast milk production as obtained from the results of qualitative evaluations through interviews and group discussions. This activity received a positive response from participants and local health workers, and is recommended for routine implementation in community midwifery services.